Plaintiff Culpability and the New Zealand Tort of Invasion of Privacy - Tat, Lisa (Victoria University of Wellington Law Review, 2008)
The tort of invasion of privacy is still a relatively new cause of action in New Zealand, which means that there are many novel issues that the courts will face in future cases that require consideration. One such issue is that of plaintiff culpability. While the concept is not entirely novel, it is yet to be examined in depth. The concept was discussed in the High Court decision of Andrews v TVNZ and the case forms the basis of analysis in this article. Drawing on case law from New Zealand and the United Kingdom the article examines the concept of plaintiff culpability and determines what it means and how it should be considered in an invasion of privacy action. The facts of Andrews v TVNZ are revisited to illustrate how the results of the analysis might be applied in future cases.